2012
DOI: 10.1016/j.crohns.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability, and predictors of response to infliximab therapy for Crohn's disease: A large single centre experience

Abstract: Background: Infliximab is licenced for use in Crohn's disease (CD). Trial data demonstrate that infliximab is effective for inducing remission of active CD, healing fistulising CD, and preventing relapse once in remission. However, long-term data regarding efficacy, safety, and predictors of response are still emerging. Aim: To examine these issues in a large cohort of patients who received infliximab for CD. Methods: A retrospective analysis of prospectively collected data was performed for 210 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 25 publications
6
99
4
3
Order By: Relevance
“…The medical records of 492 unselected patients (or 464 with outcome data, used here as the denominator to calculate rates) treated with infliximab at the Mayo Clinic (1998-2002) were systematically reviewed. The study showed an 86 % initial response rate (or 80 % calculated on an ITT basis), similar to the 82-89 % reported in most other publications such as the pediatric REACH trial [5], the Edmonton cohort [6], the large Leuven cohort [7], the Leeds cohort [8], and the Targan initial RCT [1] but higher than the short-term response rate achieved in the ACCENT trial (65 %) [2]. This figure (82-89 %) also includes those with partial response, variably defined in the different studies.…”
supporting
confidence: 85%
“…The medical records of 492 unselected patients (or 464 with outcome data, used here as the denominator to calculate rates) treated with infliximab at the Mayo Clinic (1998-2002) were systematically reviewed. The study showed an 86 % initial response rate (or 80 % calculated on an ITT basis), similar to the 82-89 % reported in most other publications such as the pediatric REACH trial [5], the Edmonton cohort [6], the large Leuven cohort [7], the Leeds cohort [8], and the Targan initial RCT [1] but higher than the short-term response rate achieved in the ACCENT trial (65 %) [2]. This figure (82-89 %) also includes those with partial response, variably defined in the different studies.…”
supporting
confidence: 85%
“…In a Canadian cohort of 130 patients, most on concurrent immunomodulators, 83 % maintained clinical response at 30 weeks and 64 % at 54 weeks [ 60 ]. Another study detailing a large single center experience with infl iximab showed an 82 % response to infl iximab induction, and a 66 % sustained clinical benefi t [ 61 ].…”
Section: Tumor Necrosis Factor-alpha (Tnf-α) Inhibitorsmentioning
confidence: 96%
“…Smoking, long (>2 years) disease duration, small bowel extent of disease, complicated phenotype and prior failure of another anti-TNF agent are found in some, albeit not all, studies to confer an increased risk of primary nonresponse in CD [272][273][274][275]. Increased age, anti-neutrophil cytoplasmic antibody (ANCA)-positive status and anti-Saccharomyces cerevisiae antibody (ASCA)-negative status and prior anti-TNF exposure are risk factors for primary nonresponse in patients with UC [276,277].…”
Section: Adl: the Development Of Anti-mab Antibodies Has Beenmentioning
confidence: 97%